2021
DOI: 10.33399/biibfad.835976
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Determinants of Household Health Expenditures in Turkey Using Simultaneous Quantile Regression Method

Abstract: düzeyi (lise, üniversite ve üzeri), hanede 0-5 yaş ve engelli birey varlığı ile toplam sağlık harcaması arasında pozitif ilişki olduğu görülmüştür. Bütün kantillerde kentte yaşayan haneler ve evli hanehalkı reislerinin bulunduğu hanelerin daha fazla toplam sağlık harcaması yaptığı görülmüştür. Q75. kantilde hanehalkı reisinin erkek olmasının toplam sağlık harcamalarını azalttığı görülmüştür. Kantillerdeki detaylar ve bulgular sonuç kısmında kapsamlı bir şekilde açıklanmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
2
1
1
Order By: Relevance
“…Yıldırım et al (2011) find no statistically significant correlation between OOP healthcare spending and gender, which is consistent with the findings of this study. Contrary to the findings of this study, Ercan (2021) shows a negative association between the male gender and OOP healthcare spending. This study also finds that good and excellent health status decreases OOP healthcare spending; the result is incomparable as the data previously used in the Turkish context does not have this information within the data set.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Yıldırım et al (2011) find no statistically significant correlation between OOP healthcare spending and gender, which is consistent with the findings of this study. Contrary to the findings of this study, Ercan (2021) shows a negative association between the male gender and OOP healthcare spending. This study also finds that good and excellent health status decreases OOP healthcare spending; the result is incomparable as the data previously used in the Turkish context does not have this information within the data set.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies on Türkiye do not control these types of income measures due to the nature of the data they employed, so the result is not comparable in the Turkish context. The negative relationship between educational attainment and OOP health spending is well established (see Demir et al (2011); Ercan (2021); İpek (2019); Yıldırım et al ( 2011)) and found in this study as well. As mothers are the primary caregivers of the children within a family, the education of mothers might play a significant role in the health outcome of individuals.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Çınar [16], simülasyon yoluyla uç değer içeren bağımlı ve bağımsız değişkenler kullanarak KR modelini incelemiştir. Literatürde çeşitli sorunları yorumlamak ve bu sorunları etkileyen faktörleri belirleyebilmek için sosyal dışlanmışlık [17], sağlık [18]- [21] ve ekonomi [22], [23] alanlarında da KR modelinin kullanıldığı bilinmektedir. KR analizinin, küresel iklim değişiklikleri, ekonomi, biyoloji, tıp, mühendislik, biyomedikal ve diğer sağlıkla ilgili araştırmalarda, genetik, halk sağlığı, biyoinformatik, ücret eşitsizlikleri, gelir düzeyinin belirlenmesi ve yaşam analizi gibi farklı alanlarda kullanıldığı bilinmektedir.…”
Section: Introductionunclassified